Problematika Guru Dalam Menerapkan Kurikulum Merdeka di Madrasah Ibtidaiyah - Anisa Septiliani; Waseso, Hendri Purbo (Journal of Primary Education Studies, 2025)
This research aims to outline and identify various problems that arise in the implementation of the Merdeka Curriculum by teachers at Islamic Elementary School. The method used is descriptive qualitative, with data collection through observation, interviews and documentation. The main focus of this research is how the Independent Curriculum is implemented and the challenges faced by teachers. Subjects involved in the research include principals, teachers, and students. The research results show that the independent curriculum has been implemented starting in the 2023/2024 academic year. Direct implementation without adequate preparation or training can be an obstacle to implementation. In its implementation, teachers are required to develop learning achievements, design learning objectives, develop learning objectives, develop projectbased teaching, and apply learning that supports strengthening the profile of Pancasila students. This is a problem because at the implementation stage, teachers experience limitations in the availability of student books, the scope of material is too broad and requires high reasoning, and difficulties in determining appropriate teaching strategies and methods. In project-based learning, teachers also experience problems in designing projects that are relevant to the material and determining appropriate forms of assessment. Meanwhile, the solution to overcome these various problems is that teachers can take part in workshops and discussion forums in teacher working groups (KKG) who participate in Merdeka Curriculum training, coordinate with colleagues, and actively seek information and references related to the implementation of the Merdeka Curriculum.